An IMD-like pathway mediates the intestinal immunity to modulate the homeostasis of gut microbiota in Rhynchophorus ferrugineus Olivier (Coleoptera: Dryophthoridae). (August 2019) - Xiao, Rong; Wang, Xinghong; Xie, Erming; Ji, Tianliang; Li, Xiongwei; Muhammad, Abrar; Yin, Xianyuan; Hou, Youming; Shi, Zhanghong
Abstract: Most animals have established the mutualistic interactions with their intestinal microbes which provide multiple benefits to their host physiology. However, the mechanisms behind hosts determine the load and composition of gut microbiota are still poorly understood outside dipteran insects. Here, the gene, encoding the NF-κB-like transcription factor Relish, being designated as RfRelish, was identified and analyzed in red palm weevil (RPW), Rhynchophorus ferrugineus Olivier. We revealed that the abundance of RfRelish transcripts in the fat body, hemolymph and gut are significantly higher than that in non-immunity-related tissues, and its expression level can be markedly induced by bacterial challenges. When RfRelish was silenced, the ability of individuals to clear the pathogenic bacteria in body cavity and gut was significantly compromised, suggesting that both the systemic and gut local immunity were impaired dramatically by RfRelish knockdown. Additionally, the silenced insects exhibited increased gut bacterial load, and the relative abundance of some gut bacteria was changed as compared to controls. Collectively, our findings demonstrate that the IMD-like pathway restricts the proliferation of gut bacteria and shapes the commensal community structure in the intestine of R . ferrugineus by mediating the secretion of antimicrobial peptides. We provide a striking example on how an insect pest maintains the homeostasis of gut microbiota via a conserved immune pathway without compromising the advantages of the mutualistic relationships. Highlights: RfRelish -mediated IMD-like pathway was identified in the alien pest (RPW) Rhynchophorus ferrugineus Olivier. RfRelish expresses strongly in fat body, hemolymph and gut as compared to other non-immunity-related tissues. Pathogen clearance in body cavity and intestine was drastically dampened by RfRelish inhibition. The load of endogenous gut microbiota was intensively increased and its composition was altered by RfRelish knockdown. The IMD-like pathway modulates RPW intestinal microbiota by mediating the secretion of antimicrobial peptides.